Pengaruh Motivasi Dan Disiplin Terhadap Produktivitas Kerja Karyawan Di Sekolah Alam Al-Giva Bogor - Rinda, Rachmatullaily Tinakartika; Dali, Rahmat Mulyana; Erpiyani, Resti (INOVATOR, 2014)
This study aims to detemine the effect of motivation and discipline on the work productivity of employees at the School Alam Al-Giva Bogor. The purpose of this study is to use quantitative research methods to determine whether motivation and discipline affect employee productivity. The sources used are primary and secondary data. The data analysis method used is multiple linear regression analysis method obtained by using the SPSS 28 program. The data collection method was carried out by distributing questionnaires to 40 respondents. Overall, the results of multiple linear analysis and hypothesis testing concluded that simultaneously motivation and discipline had a positive and significant effect, with Fcount > Ftable of 21.942 > 3.24 and an R Square value of 0.478 or 47.8%, which means that there is an influence of motivation and discipline on work productivity. Employees by 47.8% other variables not seen from this study. So it can be concluded from this study that the motivation variable has a significant effect on employee work productivity as well as the discipline variable which has a significant influence on employee work productivity.